SILK - Baluch, Matúš (Vysoké učení technické v Brně. Fakulta výtvarných umění)
Diplomová práca vychádza z metaforicky řečeno rán na fyzickom psychickom i sociálnom tele žitej performancie, kterú použitím prostředku instalace a doplnením textu s otvorenou možnosťou vo všetkých jeho podobách dostávam do jiného diskurzu.

My diploma thesis is instalation, which elements are based on principales of ready-made. Documentation of living performance. Site-specific charakter, objects, and documents are common, that are one from of physical, psychical, and social injuries. Trought the installation and added text with its full range of form I am changing the discurse.
SILK
Keywords: Trpělivost; umenie; neumenie; instalce; text; dokument; relax art; diferenciace; změna diskurzu; jméno; péro; anonym; performance; ready-made; mady-raid; kouzelnícky trik; školský kontext; pamět; image; trapnost; překlad; kříž; free art; domáci práce; fake art; alibi art; art as art; looser; čo ja viem?; riziko; hranice umenia; neporozumnění; body art; social art; uvnitř a venku; návrat domů; človek; znak; jazyk; já; penis; zmizení; Copy or translate; identity; legend; installation; non-identification; language; body-art; fake-art; alibi; krimi; art; text; liquid identity; disappearing of person; me and not me; image; performance; ready-made; mady-raid; black image white head; erorr; dick; provocation